Anesthesia and the fetus - Ginosar, Yehuda (Chichester, West Sussex : Wiley-Blackwell, 2013)
'This book covers all aspects of anesthesia affecting the fetus throughout in utero life. The book comprises three sections looking at: 1) endpoints for fetal and neonatal outcomes, 2) anesthetic interventions that may affect these endpoint variables, and 3) confounding variables which may modify the effects of anesthesia and analgesia on outcomes. A concise, pratical guide backed up by theory, it also discusses wider ethical and legal considerations. With increasing uses of anesthesia throughout pregancy, this book makes anesthetists and obstetricians aware of the potential affects of anesthetics on fetal development and outcomes'--Provided by publisher.
Section 1: Basic Principles. Intrauterine Growth and Development / Timothy J M Moss, Cheryl A Albuquerque, Richard Harding -- Maternal Physiological Adaptations to Pregnancy / Julie Phillips, Melissa Covington, George Osol -- Placental Respiratory Gas Exchange / Lowell Davis -- The Fetal Circulation / Loren P Thompson, Kazumasa Hashimoto -- Fetal Responses to Hypoxia / Tania L Kasdaglis, Ahmet A Baschat -- Pharmacokinetics in Pregnancy / Janine R Hutson, Chagit Klieger, Gideon Koren -- The First Few Breaths: Normal Transition from Intra- to Extra-Uterine Life / Smadar Eventov-Friedman, Benjamin Bar-Oz -- Section 2: Endpoint Variables: Assessments of Fetal Wellbeing and Neonatal Outcome. Validity of Endpoint Measurement / Pamela J Angle, Stephen Halpern, Marcos Silva Restrepo, Alexander J Kiss -- Imaging of the Fetus and the Uteroplacental Blood Supply: Ultrasound / Kypros Nicolaides -- Imaging of the Fetus and the Uteroplacental Blood Supply: MRI / Caroline Wright, Philip Baker -- Fetal Heart Rate Monitoring / Alison M Premo, Sarah J Kilpatrick -- Fetal Acid-Base Monitoring / Lennart Nordstrom -- Fetal Pulse Oximetry / Paul B Colditz, Christine East -- Neonatal Assessment and Prediction of Neonatal Outcome / Vadivelam Murthy, Anne Greenough -- Section 3: Interventions: Anesthesia, Analgesia, and their Effects on the Fetus. Environmental Exposure to Anesthetic Agents / Asher Ornoy -- Anesthesia and Analgesia for Assisted Reproduction Techniques and other Procedures during the First Trimester / Arvind Palanisamy, Lawrence C Tsen -- The Effect of Anesthetic Drugs on the Developing Fetus: Considerations in Non-Obstetric Surgery / Richard S Gist, Yaakov Beilin -- Substance Abuse and Pregnancy / Donald H Penning, Allison J Lee -- Intrauterine Fetal Procedures for Congenital Anomalies / Amar Nijagal, Hanmin Lee, Mark Rosen -- The EXIT procedure / Sheldon M Stohl, Hindi E Stohl, Ari Y Weintraub, Kha M Tran -- Mechanisms and Consequences of Anesthetic-Induced Neuroapoptosis in the Developing Brain / Zhaowei Zhou, Adam P Januszewski, Mervyn Maze, Daqing Ma -- Relevance to Clinical Anesthesia of Anesthetic-Induced Neurotoxicity in Developing Animals / Catherine E Creeley, Mervyn Maze, John W Olney -- External Cephalic Version / Carolyn F Weiniger, Yossef Ezra -- Effects on the Fetus of General Versus Regional Anesthesia / Sharon Orbach-Zinger, Yehuda Ginosar -- Anesthesia for Cesarean Delivery: Effects on the Fetus of Maternal Blood Pressure Control / Warwick D Ngan Kee -- Effects on the Fetus of Maternal Oxygen Administration / Neeti Sadana, Scott Segal -- Effects on the Fetus of Maternal Position During Cesarean Delivery / Robin Russell -- Effects on the Fetus of Systemic vs. neuraxial analgesia / Stephen H Halpern, Marcos Silva Restrepo -- The Effects on the Fetus of Early Versus Late Regional Analgesia / Cynthia A Wong -- Regional Analgesia, Maternal Fever, and its Effect on the Fetus and Neonate / Tabitha A Tanqueray, Philip J Steer, Steve M Yentis -- Effects on the Fetus of Major Maternal Anesthetic Complications / Felicity Plaat, Ruth Bedson -- Section 4: Confounding Variables: The Compromised Fetus, the Compromised Mother. Multiple Pregnancy / Yehuda Habaz, Jon Barrett, Eric S Shinwell -- Preeclampsia: The Compromised Fetus, the Compromised Mother / Todd R Lovgren, Henry L Galan -- Fetal Distress / Robert A Dyer, Leann K Schoeman -- Section 5: Trauma and Resuscitation. Maternal Trauma / Yuval Meroz, Uriel Elchalal, Avraham I Rivkind -- Maternal Resuscitation and Perimortem Cesarean Delivery / Sharon Einav, Sorina Grisaru-Granovsky, Joseph Varon -- Intrauterine Fetal Resuscitation / Stephen Michael Kinsella, Andrew Shennan -- Neonatal Resuscitation and Immediate Neonatal Emergencies / Ritu Chitkara, Anand K Rajani, Louis P Halamek -- Section 6: Medicine, Ethics, and the Law. Fetal Beneficence and Maternal Autonomy: Ethics and the Law / William J Sullivan, Joanne Douglas -- Maternal-Fetal Research in Pregnancy / Frank A Chervenak, Laurence B McCullough.
Includes bibliographical references and index.
Print version record.
Keywords: Anesthesia in obstetrics; Anesthesia, Obstetrical -- adverse effects; Embryonic and Fetal Development -- drug effects; Anesthetics -- adverse effects; Fetal Monitoring; Fetus -- Drug effects; Pregnancy Outcome; Electronic books